Social dynamics and sexual segregation of Australian humpback dolphins (Sousa sahulensis) in Moreton Bay, Queensland. Issue 2 (2nd December 2019) - Hawkins, Elizabeth R.; Pogson‐Manning, Lara; Jaehnichen, Christian; Meager, Justin J.
Abstract: Understanding the social organization of coastal dolphins, particularly those that reside adjacent to major cities and urbanized regions, is important for understanding the vulnerability of populations to human impacts. We investigated the sexual segregation and social dynamics in a population of Australian humpback dolphins ( Sousa sahulensis ) inhabiting the near‐urban embayment of Moreton Bay, Queensland. Over 160 vessel‐based surveys, 148 adults were photographically identified. This included 116 assumed females and 32 assumed males. The population was sexually segregated (SSAS = 0.52, p  < .001) and individuals preferred to associate with others of the same sex occupying the same spatial area ( p  < .025). Association indices between paired males were almost double those of females ( x ¯ HWI = 0.09, SD = 0.04 and x ¯ HWI = 0.05, SD = 0.02, respectively). However, females were more gregarious than males and maintained a larger network of associates based on preferred companionships. The social network was also modular with five clusters identified, and a limited number of individuals had a disproportionate influence on connectivity between clusters. This highly fragmented social network implies that the population may be vulnerable to social disruptions from human impacts.